Ilmu dan Agama dalam Perspektif Filsafat Ilmu - Ahmadi Ahmadi; Afroh Nailil Hikmah; Agus Yudiawan (Al-Fikr: Jurnal Pendidikan Islam, 2021)
This paper aims to understand the two basic concepts that are the focus of the discussion, namely science and religion through a philosophy of science approach. This approach assumes seeing the foundation that allows the development of theoretical arguments about the nature of science (knowledge, science) and religion studied in the basic concepts of Philosophy of Science. The Philosophy of Science that is meant must have been formulated in a contextual-humanist-sociological manner that is social salvation. So that it can make a significant contribution to humanity as a whole. Thus, the Philosophy of Science will dynamically always be in line with the main mission of Islam, namely rahmatan Lil 'ālamīn.